2012
DOI: 10.1097/paf.0b013e3181d3dc24
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Cricoid as a Potential Pointer to Homicide

Abstract: The distinction of a suicidal hanging from a simulated hanging following a homicidal strangulation is highly challenging. The present study evaluates the fracture of the cricoid cartilage as a potential pointer toward homicide. Despite the numerous studies on neck structures fractures in hanging, this is the first study to concentrate on the cricoid cartilage. Neck structures fractures in all cases of suicidal hanging over a 6-year period were retrospectively reviewed (231 cases) and a comparison with homicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the literature, the incidence varies widely from one study to the next, from 0 to 76.8% [4][5][6]. This variation is not surprising considering that the expected incidence will vary significantly depending on the proportion of older people in the series.…”
Section: General Incidence Of Fracturementioning
confidence: 97%
See 1 more Smart Citation
“…In the literature, the incidence varies widely from one study to the next, from 0 to 76.8% [4][5][6]. This variation is not surprising considering that the expected incidence will vary significantly depending on the proportion of older people in the series.…”
Section: General Incidence Of Fracturementioning
confidence: 97%
“…The incidence of such fractures varies from one study to the next, from 0 to 76.8% [4,5]. In a recent paper, a meta-analysis of all English studies revealed an incidence of neck structure fractures of 36.6% AE 24.7 [6]. The majority of these fractures are isolated thyroid cartilage fracture (15.3% AE 12.1), followed by isolated hyoid bone fracture (11.5% AE 12.1) and combined thyroid cartilage and hyoid bone fracture (7.5% AE 6.1).…”
Section: Introductionmentioning
confidence: 97%
“…Another study, published in 2009, examined the significance of Simon's haemorrhage in a case series consisting only of hangings, where a total of 178 hanging cases were observed and analysed to evaluate how many presented Simon's sign and how many did not [27]. In 2009, a group of Canadian authors investigated the diagnostic value of cricoid cartilage lesions in relation to hanging, particularly in terms of differential diagnosis with homicide [28]. In 2018, a study by Swiss authors analysed the intervertebral vacuum phenomenon (VP).…”
Section: Discussionmentioning
confidence: 99%
“…Godin et al. [ 77 ] reported that fracture of the cricoid is rare in suicidal hangings but common in homicidal strangulation. In cases of possible simulated hanging following homicidal strangulation [ 78 ], cricoid fracture may be a significant finding.…”
Section: Causesmentioning
confidence: 99%